Design and Development of An Automatic Door Gate Based on Internet of Things Using Arduino Uno - Arnawan Hasibuan; Rosdiana Rosdiana; Dewi Sartika Tambunan (Bulletin of Computer Science and Electrical Engineering, 2021)
This study aims to design a prototype of an automatic gate drive by utilizing a DC motor in order to be able to control the house gate automatically and be able to open the door or close the door by using an application on a Smartphone. The drive system uses a DC motor with a supply voltage given from a 12 V battery installed on the prototype turnstile. so that the DC motor can open and close properly it requires serrations on the gate according to the size of the teeth (gear). Besides that, the components are arranged in the Arduino uno circuit using the HC-05 Bluetooth module, Motor Driver l298n as a polarity reverser for the DC motor, the fence as a load, and the Bluetooth RC Controller application to be able to input so that the DC motor can move according to the commands given.